Decision Support System for Identifying Fire Prone Areas Using the Fuzzy Analytical Hierarchy Process Method - Rahmawati, Nesya Nuur; Aprillya, Mala Rosa; Ardiansyah, Heri (Universitas Muhammadiyah Lamongan, 2024)
Fire is a harmful and difficult-to-control blaze. Recently, the occurrence of fires has often been caused by factors such as human error. This research aims to develop a decision support system to help identify fire-prone areas in the village of Made, Lamongan Regency. The study incorporates several criteria, including distance from water sources, road width, building materials, and population density. Data for this research was collected from all 27 districts, 12 sub-districts, and 476 villages in Lamongan Regency.The development of this system begins with the collection of relevant data, including the distance from water sources, road width, building materials, and population density in the village of Made. The subsequent step involves designing the decision support system using the Fuzzy Analytical Hierarchy Process (FAHP) method. The calculation of fire-prone areas is carried out using the FAHP method. Subsequently, a web-based system is built using the PHP programming language. The results indicate that this system is capable of providing information on fire-prone areas with an average user satisfaction rate of 81.6%. Keywords- Decision Support System; FHP; Fire; Lamongan.